Tunneling time through a rectangular barrier - de Aquino, Veríssimo M.; Aguilera-Navarro, Valdir C. [UNESP]; Goto, Mario; Iwamoto, Hiromi (American Physical Society (APS), 1998)
In this paper, we discuss the tunneling time of a quantum particle through a rectangular barrier. The reflection and transmission times associated with the wave packets representing the particle are discussed. By using an initial Gaussian momentum distribution, we carry out a comparative analysis of the stationary phases of the incident, reflected, and transmitted wave packets leading to the reflection and transmission times [Formula Presented] and [Formula Presented] respectively. In the present treatment of this old and very known problem we take into account the deformations of the reflected and transmitted momentum distributions. These deformations produce a dependence of the reflection and transmission times on the location of the initial wave packet. In a parallel calculation, by numerically monitoring the time evolution of the system, we characterize a reflection and a transmission time. Such times agree with the ones obtained via the stationary phase method. © 1998 The American Physical Society.